Interpreting the Qur'an in a Corruption-Laden Space: Muhammadiyah's Anti-Corruption Discourse in Tafsir At-Tanwir - Al Majid, Akhlis; Saputra, Ali Thaufan Dwi (Universitas Muhammadiyah Surakarta, 2025)
This study examines Tafsir At-Tanwir, the official Qur'anic commentary of Muhammadiyah, as a form of interpretation grounded in the contemporary social realities of Indonesia. Using a descriptive-critical approach with thematic categorization, the research reveals that its anti-corruption discourse is constructed through three main perspectives: as a deviation from the principle of tawhid (divine unity), as a failure to integrate worship with social ethics, and as a consequence of neglecting Islamic values in leadership and wealth management. The analysis demonstrates that rather than adopting a neutral stance, the commentary explicitly positions itself as part of Muhammadiyah's ideological da'wah strategy to realize an ideal Islamic society. Thus, Tafsir At-Tanwir is not merely an explanatory text of sacred verses but also a powerful tool for social transformation.